Analysis of experiential marketing, trust, convenience and digital marketing on purchasing decisions on the shopee application - Siregar, Nurintan; Laksono, Agung; Hansyah, Praida (Institute of Computer Science (IOCS), 2024)
The large number of internet users, especially in Indonesia, provides a great opportunity for business people to create online shopping. This research aims to determine the influence of experiential marketing, trust, convenience, and digital marketing on purchasing decisions on the Shopee application. The population in this study are customers who use Shopee at Labuhanbatu University. The data source used is primary data. Data collection was carried out through distributing questionnaires with a sample size of 150 respondents. The analysis technique used in this research is multiple linear regression analysis technique using the SmartPLS tool. The research results show that experiential marketing, trust, convenience, and digital marketing simultaneously and partially have a significant influence on the purchasing decisions of Shopee users in Labuhanbatu. From this research, the most dominant variable is convenience at 0.495 or 49.5%. The R2 test results prove that the model is able to explain the dependent variable studied, namely the purchasing decision variable of 0.746 or 74.6%.